Culturable fungal diversity associated with forest leaf litter from Bhandara District of Maharashtra, India - SUNIL M. AKARE; WALAY Y. TAGADE; ASHNISH R. WARGHAT; AVILEKH NARYAL; ASHWANI BHARDWAJ (Biodiversitas Journal of Biological Diversity, 2016)
Akare SM, Tagade WY, Warghat AR, Naryal A, Bhardwaj A. 2016. Culturable fungal diversity associated with forest leaf litter from Bhandara District of Maharashtra, India. Biodiversitas 17: 349-358. Diversity of leaf litter fungi were carried out in 201011. Four samples were collected from Bampewada and Sakoli forest area of Bhandara District of Maharashtra, India. The Blotter paper method, Segment plate method and Serial dilution methods were used to assess the diversity of fungal species. Fungi were cultivated on potato dextrose agar, malt extract agar and czapek dox agar. A total of 31 species comprising 29 Ascomycetes and two Zygomycetes were recognized from 4 samples collected from Bampewada and Sakoli forest area. The most abundant group was Ascomycetes. The dominant species in both the forests were A. flavus, A. niger, Aureobasidium sp., Fusarium oxysporum, Penicillium sp.1, Rhizopus stolonifer, A. caespitosus, Penicillium sp.2, A. nidulans, Helminthosporium sp. and Monodictys fluctuata. While, common species were A. flavus, A. fumigatus, A. nidulans, A. niger, Beltrania rhombica and Fusarium oxysporum. The fungal diversity was higher in theSakoli forest than that of Bampewada forest. Differences were observed in percentage occurrence of fungal species between two forest areas. The reason may be that the quality of litters, different microenvironments and other characteristics in the Sakoli forest provided more resources for fungi than in Bampewada forest.